Diluting substantive equality: why the UK government doesn't know if its welfare reforms promote equality - Roberts, Simon; Stafford, B.; Hill, Katherine (Emerald, 2017)
The UK Coalition government introduced a raft of welfare reforms between 2010-2015. As part of its response to the financial crisis reforms were designed to cut public expenditure on social security and enhance work incentives. Policy makers are required by legislation to have due regard to the need to eliminate discrimination, advance equality of opportunity, and foster good relations between different people. This Public Sector Equality Duty is an evidence-based duty which requires public authorities to assess the likely effects of policy on vulnerable groups. This chapter explores the extent to which the Department for Work and Pensions adequately assessed the equality impacts of key welfare reforms when policy was being formulated. The chapter focuses on the assessment of the impact of reductions to welfare benefits on individuals with protected characteristics - age, disability, gender, gender reassignment, marriage and civil partnership, pregnancy and maternity, race, religion and belief, and sexual orientation - including individual and cumulative impacts. It also considers mitigating actions to offset negative impacts and how the collection of evidence on equality impacts was used when formulating policy. The chapter shows that the impacts of the reforms were only systematically assessed by age and gender, and, where data were available, by disability and ethnicity with no attempt to gauge cumulative impacts. There is also evidence of Equality Impact Assessments finding a disproportionate impact on individuals with protected characteristics where no mitigating action was taken.